Aging of 0-3 piezoelectric PZT ceramic-Portland cement composites - Chaipanich A. (Elsevier Ltd, 2014)
New piezoelectric-cement composites have recently been developed in order to provide compatibility to the concrete structures where the composites can act as sensors for smart structure health monitoring applications. In this work, lead zirconate titanate (PZT) was mixed with normal Portland cement at 30-50% by volume to produce 0-3 connectivity composites and the effect of age up to 1 year on the piezoelectric coefficient (d33) of PZT-cement composite after poling was investigated. The d33 value of the 50% PZT composite measured at 24 h after poling is 26 pC/N and this value increased significantly during the first 10 days before reaching a value of ≈60 pC/N at 30 days and 90 days, with no significant difference at 1 year. The increase in the piezoelectric coefficient with age is believed to be due to both the reduction in the pores within the cement matrix due to hydration and moisture responsible for the transportation of ions. When compared the electromechanical coupling coefficient results between 1 month and 1 year, ≈1.5% difference was found between the two testing periods. © 2014 Elsevier Ltd and Techna Group S.r.l.